Investigation of tool wear and surface finish by analyzing vibration signals in turning assab-705 steel - Bhuiyan, M.S.H.; Choudhury, I.A. (2015)
Various occurrences in machining influence the machining dynamics and thus produce vibration in the cutting tool-workpiece arrangement. In this investigation, with tri-axial accelerometer mounted on the tool-holder in turning ASSAB-705 steel, vibration signals have been captured with and without cutting. The nature of vibrations arising in the cutting tool at different cutting conditions has been investigated. It has been observed that the RMS amplitude of vibration along all three axes for the increasing cutting speed was mixed in nature; however, an increasing trend was noticed in the vibrations along the feed, V-x and radial, V-y directions. The vibration along the main cutting direction, V-z was mixed, initiated by large vibration and then decreased until a particular cutting speed was reached and finally increased steadily. The feed vibration component, V-x has a similar response to the change of the workpiece surface roughness, while the other two components, V-y and V-z have the more coherent response to the rate of flank wear progression throughout the tool life. The natural frequency of different machine parts vibration has been found to be within the band of 0Hz - 4.2kHz, whereas the frequencies of different occurrences in turning varied between 98Hz and 42kHz.